Um algoritmo para estimar a dimensão do segundo grupo de homologia de um grupo finitamente apresentado - VIEIRA, Flavio Pinto (2012)
The main goal of this work is to establish a primary bound for the dimension of the second homology group of a group G, with coefficients in a field k of characteristic p, H2(G;k), using the operating system GAP. It will be presented with several examples, where in some cases, will be calculated the exact dimensions and in other cases only an upper bound.